High-strength lightweight polyurethane composite material

By using crosslinked polyurethane, hollow carbon balls and other constituent materials and specific process treatments, high-strength lightweight polyurethane composite materials are prepared, which solves the problems of lightweight and insufficient flame retardant performance of existing materials, and achieves significant improvement in mechanical performance and improvement of material compatibility.

CN119708823APending Publication Date: 2025-03-28TUOCHUANG INTELLIGENT MFG (JIANGSU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411943193.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The lightweight and flame retardant properties of existing polyurethane materials need to be further improved.

Method used

The high-strength lightweight polyurethane composite material was prepared by the process of a twin-screw extruder and an autoclave.

Benefits of technology

It significantly improves the lightweight and flame retardant properties of the material, enhances the mechanical and wear resistance of the material, and improves the compatibility of the material with inorganic auxiliary materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The invention discloses a high-strength light-weight polyurethane composite material, belongs to the technical field of polyurethane preparation, and is used for solving the technical problem that the light-weight performance and flame-retardant performance of a polyurethane material in the prior art need to be further improved. The composite material comprises the following raw materials in parts by weight: 80-100 parts of cross-linked polyurethane, 10-15 parts of hollow carbon spheres, 3-5 parts of a heat stabilizer, 4-6 parts of a lubricant and 3-5 parts of an antioxidant, the hollow carbon spheres are prepared to serve as a reaction monomer, a filling material and a gas discharging center, the density of the material is reduced while foaming of the material is promoted, the strength of the material is enhanced, and the prepared flame-retardant cross-linking agent is hybridized with a polyurethane chain segment and cooperates with a flame-retardant curing agent to enhance the flame-retardant performance of the material. The siloxane structure of the flame-retardant curing agent enhances the wear resistance of the material and enhances the compatibility of the material and inorganic auxiliary materials, so that the mechanical properties of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane processing, and in particular to a high-strength and lightweight polyurethane composite material. Background Art

[0002] The development experience of flame-retardant, wear-resistant and lightweight polyurethane materials is an evolution from traditional modification to multifunctional innovation. Polyurethane materials themselves are widely favored for their excellent elasticity, wear resistance and light weight, but their flammability limits their application in fields with high safety requirements. The synergistic modification of organic phosphorus, siloxane and nanofillers (such as silica, montmorillonite, etc.) not only effectively improves the flame retardant properties, but also maintains the mechanical strength and wear resistance of the material. At the same time, in order to meet the demand for lightweight in the aviation, automotive and construction fields, researchers have introduced lightweight fillers such as hollow glass microspheres and porous carbon to achieve high performance while reducing density. Today, flame-retardant, wear-resistant and lightweight polyurethane materials have been widely used in many fields. Future research will continue to focus on synergistic flame retardancy, environmental innovation and performance optimization, opening up broader prospects for the application of high-performance materials.

[0003] Prior art CN110964307A discloses a flame retardant and wear-resistant thermoplastic polyurethane composite material and a preparation method thereof, which is made of the following raw materials in parts by mass: 40-70 parts of thermoplastic polyurethane, 2-7 parts of boron nitride nanopowder and 0.5-1 part of boric acid, which can solve the problem of poor compatibility between thermoplastic polyurethane and boron nitride and the need to add too much filler to prepare functional materials. The flame retardancy of the obtained thermoplastic polyurethane composite material can reach V-0 level while maintaining good mechanical properties, and this method is suitable for thermoplastic polyurethane systems with a hardness of 70A-60D.

[0004] However, the above patent sprays a boron nitride dispersion on the surface of an incompletely fixed polyurethane material, and sprays boric acid on the surface of the polyurethane for curing, thereby achieving the purpose of introducing boron nitride material to improve the flame retardant properties of the polyurethane composite material; however, due to material limitations, boric acid has limited binding ability to polyurethane, and it is difficult to allow boron nitride, which has a large polarity difference with polyurethane, to exist in the polyurethane system, resulting in the material's wear resistance to be further improved, and the boron nitride material has a higher density than organic materials, which reduces the material's lightweight performance, and the source of flame retardancy mainly depends on the boron nitride material. Due to the poor wear resistance of the material, the boron nitride material will be lost, which in turn leads to the material's flame retardant properties to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a high-strength lightweight polyurethane composite material, which is used to solve the technical problem that the lightweight performance and flame retardant performance of polyurethane materials in the prior art need to be further improved.

[0007] The purpose of the present invention can be achieved through the following technical scheme: a high-strength lightweight polyurethane composite material, the polyurethane composite material includes the following raw material components in parts by weight: 80-100 parts of cross-linked polyurethane, 10-15 parts of hollow carbon spheres, 3-5 parts of heat stabilizer, 4-6 parts of lubricant and 3-5 parts of antioxidant.

[0008] Further, in step A1, the heat stabilizer is one or more of dibutyltin dilaurate, triphenyl phosphate and epoxy soybean oil; the lubricant is one or more of calcium stearate, zinc stearate and polyethylene wax; the antioxidant is one or more of antioxidant 1010, triphenyl phosphite and dilauryl sulfide; the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, 220°C, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar; in step A2, the post-treatment includes: after the insulation is completed, the reactor is lowered to room temperature, and the pressure is reduced to normal pressure at a pressure reduction rate of 0.1-0.3MPa / s, and the temperature of the reactor is raised to 40-50°C, nitrogen is continuously introduced, and the gas pressure is controlled to 1-2MPa. After constant temperature and pressure treatment for 12-24h, the pressure is quickly released to obtain a polyurethane composite material.

[0009] Further, the preparation method of the cross-linked polyurethane comprises the following steps: B1. Add polyethylene glycol, hollow carbon spheres, dimethyl biphenyl diisocyanate, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle, raise the temperature of the reaction kettle to 50-60° C., and keep the temperature for 1-2 hours to obtain a cross-linked polyurethane precursor solution; B2. Add the cross-linked polyurethane precursor liquid into the reactor, introduce nitrogen protection, raise the temperature of the reactor to 40-50°C, add the flame retardant cross-linking agent into the reactor, keep the temperature for 40-60 minutes, add the flame retardant curing agent into the reactor, keep the temperature for 20-30 minutes, and post-treat to obtain the cross-linked polyurethane.

[0010] The reaction equation for preparing cross-linked polyurethane is:

[0011] Where: ; ; .

[0012] The reaction principle for preparing the cross-linked polyurethane is as follows: in the reaction process, dimethyl diphenyl diisocyanate is used as a cross-linking agent. Under the condition of a catalyst, the isocyanate group on the dimethyl diphenyl diisocyanate acts as an active group to condense with the hydroxyl groups on polyethylene glycol and hollow carbon balls to form a polyurethane prepolymer in which the polyethylene glycol chain segments and the hollow carbon balls are co-embedded. The epoxy group on the modified chain extender can react with the isocyanate group on the polyurethane prepolymer to promote the polyurethane prepolymer to react with the active hydroxyl group on the flame retardant curing agent after esterification and cross-linking, so as to form a cross-linked polyurethane in which the polyethylene glycol chain segments and the hollow carbon balls are co-embedded and the flame retardant curing agent is combined with a silane coupling agent and a boron ester.

[0013] Furthermore, in step B1, the amount ratio of polyethylene glycol, hollow carbon spheres, dimethylbiphenyl diisocyanate, N,N-dimethylformamide and dibutyltin dilaurate is 3-5g:8-10g:6-8g:60-70mL:0.5-0.8g; in step B2, the amount ratio of cross-linked polyurethane precursor liquid, flame retardant cross-linking agent and flame retardant curing agent is 8-10g:2-3g:1-2g, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a cross-linked polyurethane.

[0014] Furthermore, the preparation method of hollow carbon spheres comprises the following steps: C1. Add tetraethoxysilane and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep warm for 24-36 hours to obtain a gel, and then post-treat to obtain a carbon sphere template; C2, adding carbon sphere template, triethylamine and acetone into a reactor and stirring, after the temperature of the reactor is raised to 50-60°C, epoxy soybean oil is added dropwise into the reactor, and the reaction is kept warm for 1-2h to obtain a self-assembled template, and then post-processing is performed to obtain a carbon package template; C3, adding the carbon-coated template and 98.0wt% sulfuric acid to a reactor at a temperature of 0-5°C and stirring, keeping the temperature and stirring for 10-15min, adding sodium chlorate to the reactor, keeping the temperature of the reactor at 0-5°C and reacting for 2-4h, adjusting the pH of the reaction system to 7 with a saturated sodium hydroxide solution, and post-treating to obtain oxidized carbon balls; C4. Add oxidized carbon spheres and 1-2 mol / L sodium hydroxide solution into a reactor and perform ultrasonication for 15-20 min at room temperature, let stand for 6-12 h, and perform post-treatment to obtain hollow carbon spheres.

[0015] Reaction principle for preparing hollow carbon spheres: The surface of the carbon sphere template prepared by hydrolysis method has a large number of hydroxyl groups. Under alkaline conditions, the epoxy groups on the epoxidized soybean oil chain segments open and self-assemble in situ on the surface of the carbon sphere template to obtain an organic layer. After high-temperature calcination and carbonization, a carbon layer is formed on the carbon sphere template to obtain a carbon-coated template. After sodium hypochlorite oxidation in a strong acid environment, the carbon layer is oxidized to form a large number of active groups such as hydroxyl groups, epoxy groups and carboxyl groups. Finally, the carbon sphere template inside the carbon layer is removed by strong alkali corrosion to obtain a hollow carbon sphere.

[0016] Further, in step C1, the stirring rate of the reactor is 60-80 rpm, the amount ratio of tetraethoxysilane, anhydrous ethanol and deionized water is 3-6 g: 30-40 mL: 10-20 mL, and the post-treatment includes: transferring the gel to a tubular furnace, introducing nitrogen protection, heating the tubular furnace to 450-500 ° C at a heating rate of 5 ° C / min, calcining for 4-6 hours, and cooling naturally to obtain a solid polymer, grinding and then 3 00-500 mesh sieve to obtain a carbon sphere template; in step C2, the amount ratio of the carbon sphere template, triethylamine, acetone and epoxy soybean oil is 5-6g:0.3-0.5g:50-60mL:8-10mL, and the post-treatment includes: transferring the self-assembled template to a tubular furnace, after nitrogen protection, the tubular furnace is heated to 700-750℃ at a heating rate of 5℃ / min, and after calcining for 4-6h, it is naturally cooled to obtain a carbon-coated template.

[0017] Furthermore, in step C3, the stirring rate of the reactor is 80-120rpm, the amount ratio of the carbon-coated template, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g, and the post-treatment includes: filtering the reaction liquid to collect the filter cake, washing the filter cake with ethanol and deionized water for 3-5 times, transferring the filter cake to a drying oven at a temperature of 60°C and vacuum drying to constant weight to obtain oxidized carbon balls; in step C4, the amount ratio of the oxidized carbon balls and 1-2mol / L sodium hydroxide solution is 1g:20-30mL, and the post-treatment includes: filtering the reaction liquid to collect the filter cake, washing the filter cake with ethanol and deionized water for 3-5 times, transferring the filter cake to a drying oven at a temperature of 60°C and vacuum drying to constant weight to obtain hollow carbon balls.

[0018] Furthermore, the preparation method of the flame retardant crosslinking agent comprises the following steps: D1, adding tripolyphosphazene chloride, 3,5-dihydroxybenzaldehyde, triethylamine and dimethyl sulfoxide into a reactor, raising the temperature of the reactor to 60-80°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain modified polyether; D2, adding the modified polyether and dimethyl sulfoxide into a reactor and stirring for 10-15 minutes, lowering the temperature of the reactor to 10-15° C., adding sodium borohydride into the reactor, keeping the temperature for reaction for 1-2 hours, and post-treating to obtain the reduced polyether; D3. Add the reduced polyether, epichlorohydrin, sodium carbonate, triethyl borate and ethyl acetate into the reactor, lower the temperature of the reactor to 0-5°C, keep the reaction warm for 1-2h, and post-treat to obtain a flame retardant cross-linking agent.

[0019] The reaction equation for preparing the flame retardant crosslinking agent is:

[0020] Where: ; ; .

[0021] The reaction principle for preparing the flame retardant crosslinking agent is as follows: the halogen groups on tripolyphosphazene chloride and the hydroxyl groups on 3,5-dihydroxybenzaldehyde undergo an elimination reaction under alkaline conditions, and the structure of the polymer is formed through the continuous reaction. After the aldehyde group is reduced to an alcohol group using sodium borohydride, an elimination reaction occurs with the halogen groups on epichlorohydrin to form a crosslinking structure, and finally the flame retardant crosslinking agent is prepared.

[0022] Further, in step D1, the amount ratio of tripolyphosphazene chloride, 3,5-dihydroxybenzaldehyde, triethylamine and dimethyl sulfoxide is 8-10g:3-5g:0.3-0.5g:40-50mL, and the post-treatment includes: after the reaction is completed, the reaction kettle is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified polyether; in step D2, the amount ratio of modified polyether, dimethyl sulfoxide and sodium borohydride is 5-6g:15-20mL:1-1.6g, and the post-treatment includes: after the reaction is completed, After that, the reaction kettle is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a reduced polyether; in step D3, the reduced polyether, epichlorohydrin, sodium carbonate, triethyl borate and ethyl acetate are used in an amount ratio of 8-10g:4-5g:1-2g:0.3-0.5g:40-60mL, and the post-treatment includes: after the reaction is completed, the reaction kettle is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a flame retardant crosslinking agent.

[0023] Furthermore, the preparation method of the flame retardant curing agent comprises the following steps: E1. Add 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde and dimethyl sulfoxide into a reaction kettle and stir for 10-15 minutes, then lower the temperature of the reaction kettle to 10-15°C, add sodium borohydride into the reaction kettle, keep the temperature for reaction for 1-2 hours, and perform post-treatment to obtain modified boric ester; E2. Add modified boric ester, 3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and deionized water into a reactor, increase the temperature of the reactor to 30-50°C, and heat-preserve for 3-5 hours, and then post-treat to obtain a flame retardant curing agent.

[0024] Reaction equation for preparing flame retardant curing agent:

[0025] Where: .

[0026] The reaction principle for preparing the flame retardant curing agent is as follows: after 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde is reduced by sodium borohydride, the aldehyde group is reduced to a hydroxyl group to obtain a modified boron ester, and under alkaline conditions, the siloxane structure on the 3-aminopropyltriethoxysilane is hydrolyzed to produce a silanol structure, which is combined with the hydroxyl group to dehydrate and obtain a flame retardant curing agent.

[0027] Further, in step E1, the amount ratio of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)benzaldehyde, dimethyl sulfoxide and sodium borohydride is 5-6g:15-20mL:1-1.6g, and the post-treatment includes: after the reaction is completed, the reaction kettle is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a modified boron ester; in step E2, the amount ratio of modified boron ester, 3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and deionized water is 5-6g:2-3g:0.3-0.5g:40-60mL, and the post-treatment includes: after the reaction is completed, the reaction kettle is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a flame retardant curing agent.

[0028] The preparation method of the polyurethane composite material comprises the following steps: A1, mixing cross-linked polyurethane, hollow carbon spheres, heat stabilizer, lubricant and antioxidant evenly, adding the mixture into a twin-screw extruder, and melt-extrude to obtain a polyurethane composite material body; A2. The polyurethane composite body is transferred to a high-pressure reactor, nitrogen is introduced into the reactor, and the air pressure is controlled to be 12-16 MPa. The temperature of the reactor is increased to 60-80° C. and the reactor is kept warm for 4-6 hours. The polyurethane composite material is obtained by post-treatment.

[0029] The present invention has the following beneficial effects: The present invention prepares a hollow carbon ball with a large number of active functional groups on the surface, which is uniformly dispersed in the polyurethane material as one of the constituent monomers of the polyurethane chain segment, and serves as a filling material and a gas release center, which promotes the foaming of the material to enhance the strength of the material while reducing the density of the material, thereby significantly improving the lightweight performance of the material. In addition, a flame retardant cross-linking agent is prepared to hybridize the polyurethane chain segment while cooperating with a flame retardant curing agent to enhance the flame retardant performance of the material, and the siloxane structure of the flame retardant curing agent enhances the wear resistance of the material while enhancing the compatibility of the material with inorganic auxiliary materials, thereby significantly improving the mechanical properties of the material. The hollow carbon spheres prepared by the present invention play the role of supporting polyurethane chain segments, filling materials and releasing gases during the foaming process during the preparation of materials, significantly improving the lightweight performance of the materials, and forming a thermal barrier on the surface of the material during the combustion process, delaying the transfer of heat to the inside, reducing the speed of thermal decomposition and flame propagation, thereby protecting the internal structure, and in the process of the flame retardant component releasing the flame retardant gas, the hollow carbon spheres serve as gas release centers, and through the slow release effect, enhance the action time and effect of the flame retardant, improve the overall flame retardant efficiency, and block oxygen and heat to inhibit the combustion reaction. The present invention also prepares a flame retardant cross-linking agent with an epoxy group as a chain extension group. During the reaction of the epoxy group with the isocyanate, the oxazolidinone generated is ring-opened at a high temperature during combustion to release carbon dioxide gas to form a three-membered ring structure, which takes away a large amount of heat, reduces the oxygen concentration, and significantly enhances the flame retardant performance. During continued combustion, the carbon-nitrogen three-membered ring continues to decompose to generate ammonia gas, further enhancing the flame retardant performance of the material. In addition, by preparing a flame retardant curing agent, a boron ester group and a siloxane structure are introduced into the polyurethane chain segment. The boron ester structure decomposes to generate boric acid to promote the carbonization of the material and form a boron oxide structure to isolate heat to achieve the purpose of improving the flame retardant performance of the material. In addition, the siloxane structure improves the compatibility of the polyurethane material and the inorganic auxiliary material, and significantly improves the wear resistance of the material. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0031] This embodiment provides a method for preparing a high-strength and lightweight polyurethane composite material, comprising the following steps: S1. Preparation of hollow carbon spheres Weigh: 10.8g tetraethoxysilane and 64.0mL anhydrous ethanol were added to the reactor and stirred at a stirring rate of 60rpm. After stirring at room temperature for 15min, 24.0mL deionized water was added dropwise. After the temperature of the reactor was raised to 40°C, 1.0mol / L ammonia solution was used to adjust the pH of the system to 8. The mixture was kept warm for 24h to obtain a gel. The gel was transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 450°C at a heating rate of 5°C / min. After calcination for 4h, the solid polymer was naturally cooled. After grinding, the carbon sphere template was obtained by passing through a 300-mesh sieve. Weigh: 10.0g carbon sphere template, 0.6g triethylamine and 100.0mL acetone are added to the reactor and stirred. After the temperature of the reactor is raised to 50°C, 16.0mL epoxidized soybean oil is added dropwise to the reactor and kept warm for 1h to obtain a self-assembled template. The self-assembled template is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 700°C at a heating rate of 5°C / min. After calcination for 4h, it is naturally cooled to obtain a carbon-coated template. Weigh: 12.0g carbon-coated template and 64.0g 98.0wt% sulfuric acid are added to a reactor at a temperature of 5°C and stirred at a stirring rate of 80rpm. After keeping warm and stirring for 10min, 6.4g sodium chlorate is added to the reactor. The temperature of the reactor is kept at 5°C for 2h. The pH of the reaction system is adjusted to 7 with a saturated sodium hydroxide solution. The reaction liquid is filtered to collect the filter cake. After washing the filter cake with ethanol and deionized water for 5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain oxidized carbon balls. Weigh: 10.0 g of oxidized carbon spheres and 200.0 mL of 1.0 mol / L sodium hydroxide solution are added to a reactor and ultrasonicated. After ultrasonication at room temperature for 15 min, the mixture is allowed to stand for 6 h. The reaction liquid is filtered to collect the filter cake. The filter cake is washed three times with ethanol and deionized water. The filter cake is transferred to a drying oven at 60 °C and vacuum dried to constant weight to obtain hollow carbon spheres.

[0032] S2. Preparation of flame retardant crosslinking agent Weigh: 16.0 g of tripolyphosphazene chloride, 6.4 g of 3,5-dihydroxybenzaldehyde, 0.8 g of triethylamine and 84.0 mL of dimethyl sulfoxide, add them into a reactor, raise the temperature of the reactor to 60° C., and keep the temperature for 2 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain a modified polyether; Weigh: 10.0 g of modified polyether and 32.0 mL of dimethyl sulfoxide are added to a reactor and stirred for 10 min. The temperature of the reactor is then lowered to 10° C., 2.4 g of sodium borohydride is added to the reactor, and the reaction is kept warm for 1 h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80° C., and the reduced pressure distillation is performed until no liquid is produced to obtain a reduced polyether; Weigh: 16.0g of reduced polyether, 8.4g of epichlorohydrin, 2.4g of sodium carbonate, 0.6g of triethyl borate and 84.0mL of ethyl acetate and add them to a reactor, lower the temperature of the reactor to 5°C, and keep the reaction warm for 1h. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is extracted to obtain a flame retardant crosslinking agent.

[0033] S3. Preparation of flame retardant curing agent Weigh: 10.0 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde and 30.0 mL of dimethyl sulfoxide were added to a reactor and stirred for 10 min. The temperature of the reactor was lowered to 10° C., 2.0 g of sodium borohydride was added to the reactor, and the reaction was kept warm for 1 h. After the reaction was completed, the reactor was cooled to room temperature, and the reaction solution was added to a rotary evaporator with a water bath temperature of 80° C., and the reaction solution was distilled under reduced pressure until no liquid was produced to obtain a modified boric ester; Weigh: 10.0g of modified boric ester, 4.2g of 3-aminopropyltriethoxysilane, 0.6g of saturated sodium hydroxide solution and 80.0mL of deionized water and add them into a reactor. The temperature of the reactor is raised to 30°C and kept warm for 3h. After the reaction is completed, the reactor is cooled to room temperature and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C. Distill under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.

[0034] S4. Preparation of polyurethane composite materials Weigh: 6.4 g polyethylene glycol, 16.0 g hollow carbon spheres, 12.0 g dimethylbiphenyl diisocyanate, 120.0 mL N,N-dimethylformamide and 1.2 g dibutyltin dilaurate, add them into a reactor, raise the temperature of the reactor to 50° C., keep the temperature for 1 hour, and obtain a cross-linked polyurethane precursor solution; Weigh: 16.0g of cross-linked polyurethane precursor liquid is added to the reactor, nitrogen is introduced for protection, after the temperature of the reactor is raised to 40°C, 4.2g of flame retardant cross-linking agent is added to the reactor, and the reaction is kept warm for 40min, 2.0g of flame retardant curing agent is added to the reactor, and the reaction is kept warm for 20min. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and reduced pressure distillation is performed until no liquid is extracted to obtain a cross-linked polyurethane; Weigh: 84.0 g of cross-linked polyurethane, 12.0 g of hollow carbon spheres, 3.6 g of dibutyltin dilaurate, 4.2 g of calcium stearate and 3.6 g of triphenyl phosphite, mix them evenly, add them into a twin-screw extruder, and melt-extrude to obtain a polyurethane composite material blank; The polyurethane composite body was transferred to a high-pressure reactor, and nitrogen was introduced into the reactor. After the air pressure was controlled at 12 MPa, the temperature of the reactor was increased to 60°C and kept warm for 4 hours. After the insulation was completed, the reactor was lowered to room temperature and reduced to normal pressure at a pressure reduction rate of 0.1 MPa / s. The temperature of the reactor was then raised to 40°C, nitrogen was continued to be introduced, and the air pressure was controlled at 1.0 MPa. After constant temperature and pressure treatment for 12 hours, the pressure was quickly released to obtain a polyurethane composite material. Example

[0035] This embodiment provides a method for preparing a high-strength and lightweight polyurethane composite material, comprising the following steps: S1. Preparation of hollow carbon spheres Weigh: 12.0g tetraethoxysilane and 80.0mL anhydrous ethanol were added to the reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 20min, 40.0mL deionized water was added dropwise. After the temperature of the reactor was raised to 60°C, 1.5mol / L ammonia solution was used to adjust the pH of the system to 9. The mixture was kept warm for 36h to obtain a gel. The gel was transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 500°C at a heating rate of 5°C / min. After calcination for 6h, the solid polymer was naturally cooled. After grinding, the carbon sphere template was obtained by passing through a 500-mesh sieve. Weigh: 12.0g carbon sphere template, 1.0g triethylamine and 12.0mL acetone are added to the reactor and stirred. After the temperature of the reactor is raised to 60°C, 20.0mL epoxidized soybean oil is added dropwise to the reactor and kept warm for 2h to obtain a self-assembled template. The self-assembled template is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 750°C at a heating rate of 5°C / min. After calcination for 6h, it is naturally cooled to obtain a carbon package template. Weigh: 12.0g carbon-coated template and 80.0g 98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C and stirred at a stirring rate of 120rpm. After keeping warm and stirring for 15min, 8.4g sodium chlorate is added to the reactor. The temperature of the reactor is kept at 3°C ​​and reacted for 4h. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. The reaction liquid is filtered to collect the filter cake. After washing the filter cake with ethanol and deionized water for 5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain oxidized carbon balls. Weigh: 10.0 g of oxidized carbon spheres and 30.0 mL of 2.0 mol / L sodium hydroxide solution, add them into a reactor and ultrasonicate. After ultrasonication at room temperature for 20 min, let it stand for 12 h, filter the reaction liquid to collect the filter cake, wash the filter cake with ethanol and deionized water 5 times, transfer the filter cake to a drying oven at 60 °C and vacuum dry it to constant weight to obtain hollow carbon spheres.

[0036] S2. Preparation of flame retardant crosslinking agent Weigh: 20.0 g of tripolyphosphazene chloride, 10.0 g of 3,5-dihydroxybenzaldehyde, 1.0 g of triethylamine and 100.0 mL of dimethyl sulfoxide, add them into a reactor, raise the temperature of the reactor to 80° C., and keep the temperature for 4 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain a modified polyether; Weigh: 10.0 g of modified polyether and 32.0 mL of dimethyl sulfoxide are added to a reactor and stirred for 15 min. The temperature of the reactor is then lowered to 15° C., 3.2 g of sodium borohydride is added to the reactor, and the reaction is kept warm for 2 h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100° C., and the reduced pressure distillation is performed until no liquid is produced to obtain a reduced polyether; Weigh: 16.0g of reduced polyether, 10.0g of epichlorohydrin, 4.0g of sodium carbonate, 1.0g of triethyl borate and 60mL of ethyl acetate and add them into a reactor, lower the temperature of the reactor to 0°C, and keep the reaction warm for 1h. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is extracted to obtain a flame retardant crosslinking agent.

[0037] S3. Preparation of flame retardant curing agent Weigh: 10.0 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde and 32.0 mL of dimethyl sulfoxide were added to a reactor and stirred for 15 min. The temperature of the reactor was lowered to 15° C., 3.2 g of sodium borohydride was added to the reactor, and the reaction was kept warm for 2 h. After the reaction was completed, the reactor was cooled to room temperature, and the reaction solution was added to a rotary evaporator with a water bath temperature of 100° C., and the reaction solution was distilled under reduced pressure until no liquid was produced to obtain a modified boric ester; Weigh: 10.0g of modified boric ester, 5.4g of 3-aminopropyltriethoxysilane, 0.8g of saturated sodium hydroxide solution and 120.0mL of deionized water and add them into a reactor. The temperature of the reactor is raised to 50°C and kept warm for 5h. After the reaction is completed, the reactor is cooled to room temperature and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C. Distill under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.

[0038] S4. Preparation of polyurethane composite materials Weigh: 10.0 g polyethylene glycol, 20.0 g hollow carbon spheres, 16.0 g dimethylbiphenyl diisocyanate, 140.0 mL N,N-dimethylformamide and 1.6 g dibutyltin dilaurate and add them into a reactor. The temperature of the reactor is raised to 60° C. and the reaction is kept warm for 2 h to obtain a cross-linked polyurethane precursor solution. Weigh: 20.0g of cross-linked polyurethane precursor liquid is added to the reactor, nitrogen is introduced for protection, after the temperature of the reactor is raised to 50°C, 6.0g of flame retardant cross-linking agent is added to the reactor, and the reaction is kept warm for 60min, 4.0g of flame retardant curing agent is added to the reactor, and the reaction is kept warm for 60min. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and reduced pressure distillation is performed until no liquid is extracted to obtain a cross-linked polyurethane; Weigh: 96.0 g of cross-linked polyurethane, 15.0 g of hollow carbon spheres, 4.8 g of dibutyltin dilaurate, 5.4 g of calcium stearate and 4.2 g of triphenyl phosphite, mix well and add into a twin-screw extruder, and melt extrude to obtain a polyurethane composite material blank; The polyurethane composite body was transferred to a high-pressure reactor, and nitrogen was introduced into the reactor. After the air pressure was controlled at 16 MPa, the temperature of the reactor was increased to 80°C and kept warm for 6 hours. After the insulation was completed, the reactor was lowered to room temperature and reduced to normal pressure at a pressure reduction rate of 0.3 MPa / s. The temperature of the reactor was then raised to 50°C, nitrogen was continued to be introduced, and the air pressure was controlled at 2 MPa. After constant temperature and pressure treatment for 24 hours, the pressure was quickly released to obtain a polyurethane composite material. Example

[0039] This embodiment provides a method for preparing a high-strength and lightweight polyurethane composite material, comprising the following steps: S1. Preparation of hollow carbon spheres Weigh: 9.0g tetraethoxysilane and 72.0mL anhydrous ethanol were added to the reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 20min, 30.0mL deionized water was added dropwise. After the temperature of the reactor was raised to 50°C, 1.2mol / L ammonia solution was used to adjust the pH of the system to 9. The gel was kept warm for 30h to obtain the gel. The gel was transferred to a tubular furnace. After nitrogen protection was introduced, the tubular furnace was heated to 475°C at a heating rate of 5°C / min. After calcination for 5h, the solid polymer was naturally cooled to obtain the solid polymer. After grinding, the carbon sphere template was obtained by passing through a 400-mesh sieve. Weigh: 10.8g carbon sphere template, 0.8g triethylamine and 100.0mL acetone are added to the reactor and stirred. After the temperature of the reactor is raised to 55°C, 18.0mL epoxidized soybean oil is added dropwise to the reactor and kept warm for 2h to obtain a self-assembled template. The self-assembled template is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 725°C at a heating rate of 5°C / min. After calcination for 5h, it is naturally cooled to obtain a carbon package template. Weigh: 12.8g of carbon-coated template and 72.0g of 98.0wt% sulfuric acid were added to a reactor at a temperature of 0°C and stirred at a stirring rate of 100rpm. After keeping warm and stirring for 12min, 8.4g of sodium chlorate was added to the reactor. The reactor temperature was kept at 0°C for 3h. The pH of the reaction system was adjusted to 7 with a saturated sodium hydroxide solution. The reaction liquid was filtered to collect the filter cake. The filter cake was washed 4 times with ethanol and deionized water. The filter cake was transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain oxidized carbon balls. Weigh: 10.0 g of oxidized carbon spheres and 250.0 mL of 1.5 mol / L sodium hydroxide solution are added to a reactor for ultrasonication. After ultrasonication for 18 min at room temperature, the mixture is allowed to stand for 9 h. The reaction liquid is filtered to collect the filter cake. The filter cake is washed four times with ethanol and deionized water. The filter cake is transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain hollow carbon spheres.

[0040] S2. Preparation of flame retardant crosslinking agent Weigh: 18.0 g of tripolyphosphazene chloride, 8.0 g of 3,5-dihydroxybenzaldehyde, 0.8 g of triethylamine and 90.0 mL of dimethyl sulfoxide, add them into a reactor, raise the temperature of the reactor to 70° C., and keep the temperature for reaction for 3 hours. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain a modified polyether; Weigh: 10.8 g of modified polyether and 32.0 mL of dimethyl sulfoxide were added to a reactor and stirred for 12 min, then the temperature of the reactor was lowered to 12° C., 2.4 g of sodium borohydride was added to the reactor, and the reaction was kept warm for 2 h. After the reaction was completed, the reactor was cooled to room temperature, and the reaction liquid was added to a rotary evaporator with a water bath temperature of 90° C., and the reduced pressure distillation was performed until no liquid was produced to obtain a reduced polyether; Weigh: 18.0g of reduced polyether, 9.6g of epichlorohydrin, 2.4g of sodium carbonate, 0.8g of triethyl borate and 100.0mL of ethyl acetate and add them into a reactor, lower the temperature of the reactor to 0°C, and keep the reaction for 1h. After the reaction is completed, wait for the reactor to cool to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is extracted to obtain a flame retardant crosslinking agent.

[0041] S3. Preparation of flame retardant curing agent Weigh: 10.8 g of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde and 32.0 mL of dimethyl sulfoxide were added to a reactor and stirred for 12 min. The temperature of the reactor was lowered to 12° C., 3.0 g of sodium borohydride was added to the reactor, and the reaction was kept warm for 2 h. After the reaction was completed, the reactor was cooled to room temperature, and the reaction solution was added to a rotary evaporator with a water bath temperature of 90° C., and the reaction solution was distilled under reduced pressure until no liquid was produced to obtain a modified boric ester; Weigh: 10.8 g of modified boric ester, 5.4 g of 3-aminopropyltriethoxysilane, 0.8 g of saturated sodium hydroxide solution and 100.0 mL of deionized water and add them into a reactor. The temperature of the reactor is raised to 40°C and kept warm for 4 hours. After the reaction is completed, the reactor is cooled to room temperature and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C. Distill under reduced pressure until no liquid is extracted to obtain a flame retardant curing agent.

[0042] S4. Preparation of polyurethane composite materials Weigh: 9.6 g of polyethylene glycol, 18.0 g of hollow carbon spheres, 15.0 g of dimethylbiphenyl diisocyanate, 120.0 mL of N,N-dimethylformamide and 1.2 g of dibutyltin dilaurate, add them into a reactor, raise the temperature of the reactor to 55° C., and keep the temperature for 2 h to obtain a cross-linked polyurethane precursor solution; Weigh: 18.0g of cross-linked polyurethane precursor liquid is added to the reactor, nitrogen is introduced for protection, and after the temperature of the reactor is raised to 45°C, 5.4g of flame retardant cross-linking agent is added to the reactor, and the reaction is kept warm for 50min. 3.6g of flame retardant curing agent is added to the reactor, and the reaction is kept warm for 25min. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and the reaction is distilled under reduced pressure until no liquid is extracted to obtain a cross-linked polyurethane; Weigh: 96.0 g of cross-linked polyurethane, 12.0 g of hollow carbon spheres, 4.8 g of dibutyltin dilaurate, 5.4 g of calcium stearate and 4.8 g of triphenyl phosphite, mix well and add into a twin-screw extruder, and melt extrude to obtain a polyurethane composite material blank; The polyurethane composite body was transferred to a high-pressure reactor, and nitrogen was introduced into the reactor. After the air pressure was controlled at 16 MPa, the temperature of the reactor was increased to 70°C and kept warm for 5 hours. After the insulation was completed, the reactor was lowered to room temperature and reduced to normal pressure at a pressure reduction rate of 0.2 MPa / s. The temperature of the reactor was then raised to 45°C, nitrogen was continued to be introduced, and the air pressure was controlled at 1.5 MPa. After constant temperature and pressure treatment for 18 hours, the pressure was quickly released to obtain a polyurethane composite material.

[0043] Comparative Example 1 The difference between this comparative example and Example 3 is that the step of preparing oxidized carbon spheres is eliminated in step S1, in the process of preparing hollow carbon spheres in step S1, an equal amount of carbon-coated templates are used to replace oxidized carbon spheres, and in the process of preparing cross-linked polyurethane in step S4, the use of hollow carbon spheres is eliminated.

[0044] Comparative Example 2 The difference between this comparative example and Example 3 is that the step of preparing a flame retardant crosslinking agent is omitted in step S2, and an equal amount of a reducing polyether is used to replace the flame retardant crosslinking agent in the process of preparing a crosslinked polyurethane in step S4.

[0045] Comparative Example 3 The difference between this comparative example and Example 3 is that the step of preparing a flame retardant curing agent is omitted in step S3, and an equal amount of 1,4-butanediol is used to replace the flame retardant curing agent in the process of preparing the cross-linked polyurethane in step S4.

[0046] Performance Test: The tensile strength of the polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; The density of the polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1033.2-2010 "Determination of density of non-foamed plastics Part 2: Density gradient column method"; The volume wear of the polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)"; The vertical combustion grade of the polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was determined with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of combustion performance of plastics”; The limiting oxygen index of the polyurethane composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test", and the specific data are shown in the table below.

[0047] Project Category Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 98.3 99.4 101.6 73.6 86.2 75.2 <![CDATA[Density / g·cm -3 > 0.4823 0.4723 0.4623 0.4923 0.4878 0.4723 <![CDATA[Volume wear amount / mm 3 > 32.3 31.5 29.2 63.2 45.2 64.3 Vertical burning level V-0 V-0 V-0 V-1 V-2 V-2 Limiting oxygen index / % 38.9 39.5 40.1 36.3 31.1 32.5 Data Analysis: By comparing the data in Table 1 above, the tensile strength of the polyurethane material prepared by the present invention is 101.6 MPa and the density is 0.4623 g·cm -3 , volume wear is 29.2mm 3, the vertical combustion grade is V-0 and the limiting oxygen index is 40.1%, all the data are better than the comparative example; By comparing the data of Example 3 and Comparative Example 1, it can be found that the tensile strength and wear resistance of the polyurethane composite material are significantly reduced, indicating that there is a lack of oxidation process of the carbon-coated template, and the finally prepared carbon hollow spheres lack active functional groups such as hydroxyl groups and do not participate in the preparation of cross-linked polyurethane, resulting in reduced dispersion of the carbon hollow spheres inside the material, and the efficiency of the gas release center during the foaming process is reduced, resulting in reduced foaming effect of the material, and ultimately resulting in significantly reduced tensile strength and wear resistance of the material; By comparing the data of Example 3 and Comparative Example 2, it can be found that the vertical combustion grade and limiting oxygen index of the polyurethane composite material are significantly reduced, indicating that the flame retardant cross-linking agent with hydroxyl groups as the terminal prepared in Comparative Example 2 has a simpler cross-linking structure in the process of chain extension with the polyurethane chain segment than the flame retardant cross-linking agent with epoxy groups as the terminal prepared in Comparative Example 3. The oxazolidinone produced after the reaction of the epoxy group and the isocyanate group opens the ring under the high temperature of combustion to release carbon dioxide gas to form a three-membered ring structure, which takes away a lot of heat and reduces the oxygen concentration, thereby significantly enhancing the flame retardant performance; By comparing the data of Example 3 and Comparative Example 3, it can be found that the wear resistance, vertical combustion grade and limiting oxygen index of the polyurethane composite material are significantly reduced. Compared with direct curing using 1,4-butanediol, the residual isocyanate groups in the flame retardant curing agent consumption structure introduce boron ester groups and siloxane structures into the polyurethane chain segment through chemical reactions. The boron ester structure decomposes to produce boric acid to promote carbonization of the material and form a boron oxide structure to isolate heat to achieve the purpose of improving the flame retardant performance of the material. In addition, the siloxane structure improves the compatibility of the polyurethane material and the inorganic auxiliary materials, significantly improving the wear resistance of the material. The present invention prepares a hollow carbon ball with a large number of active functional groups on the surface, which is uniformly dispersed in the polyurethane material as one of the constituent monomers of the polyurethane chain segment. The hollow carbon ball serves as a filling material and a gas release center, which promotes the foaming of the material and enhances the strength of the material while reducing the density of the material. In addition, a flame retardant cross-linking agent is prepared to hybridize the polyurethane chain segment and cooperate with the flame retardant curing agent to enhance the flame retardant properties of the material. The siloxane structure of the flame retardant curing agent enhances the wear resistance of the material while enhancing the compatibility of the material with inorganic auxiliary materials, thereby significantly improving the mechanical properties of the material.

[0048] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. High-strength and lightweight polyurethane composite material, characterized in that: The polyurethane composite material comprises the following raw materials in parts by weight: 80-100 parts of cross-linked polyurethane, 10-15 parts of hollow carbon spheres, 3-5 parts of heat stabilizer, 4-6 parts of lubricant and 3-5 parts of antioxidant; The preparation method of the cross-linked polyurethane comprises the following steps: B1. Add polyethylene glycol, hollow carbon spheres, dimethyl biphenyl diisocyanate, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle, raise the temperature of the reaction kettle to 50-60° C., and keep the temperature for 1-2 hours to obtain a cross-linked polyurethane precursor solution; B2. Add the cross-linked polyurethane precursor liquid into the reactor, introduce nitrogen protection, raise the temperature of the reactor to 40-50°C, add the flame retardant cross-linking agent into the reactor, keep the temperature for 40-60 minutes, add the flame retardant curing agent into the reactor, keep the temperature for 20-30 minutes, and post-treat to obtain the cross-linked polyurethane.

2. The high-strength and lightweight polyurethane composite material according to claim 1, characterized in that: In step B1, the amount ratio of polyethylene glycol, hollow carbon spheres, dimethyl diphenyl diisocyanate, N,N-dimethylformamide and dibutyltin dilaurate is 3-5g:8-10g:6-8g:60-70mL:0.5-0.8g; in step B2, the amount ratio of cross-linked polyurethane precursor liquid, flame retardant cross-linking agent and flame retardant curing agent is 8-10g:2-3g:1-2g.

3. The high-strength and lightweight polyurethane composite material according to claim 1, characterized in that: The preparation method of the hollow carbon sphere comprises the following steps: C1. Add tetraethoxysilane and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor rises to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the system pH to 8-9. Keep warm for 24-36 hours to obtain a silicon-based gel, which is then post-treated to obtain a carbon sphere template. C2, adding carbon sphere template, triethylamine and acetone into a reactor and stirring, after the temperature of the reactor is raised to 50-60°C, epoxy soybean oil is added dropwise into the reactor, and the reaction is kept warm for 1-2h to obtain a self-assembled template, and then post-processing is performed to obtain a carbon package template; C3, adding the carbon-coated template and 98.0wt% sulfuric acid to a reactor at a temperature of 0-5°C and stirring, keeping the temperature and stirring for 10-15min, adding sodium chlorate to the reactor, keeping the temperature of the reactor at 0-5°C and reacting for 2-4h, adjusting the pH of the reaction system to 7 with a saturated sodium hydroxide solution, and post-treating to obtain oxidized carbon balls; C4. Add oxidized carbon spheres and 1-2 mol / L sodium hydroxide solution into a reactor and perform ultrasonication for 15-20 min at room temperature, let stand for 6-12 h, and perform post-treatment to obtain hollow carbon spheres.

4. The high-strength and lightweight polyurethane composite material according to claim 3, characterized in that: In step C1, the stirring rate of the reactor is 60-80rpm, and the dosage ratio of tetraethoxysilane, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL; in step C2, the dosage ratio of carbon sphere template, triethylamine, acetone and epoxidized soybean oil is 5-6g:0.3-0.5g:50-60mL:8-10mL; in step C3, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of carbon package template, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g; in step C4, the dosage ratio of oxidized carbon sphere and 1-2mol / L sodium hydroxide solution is 1g:20-30mL.

5. The high-strength and lightweight polyurethane composite material according to claim 1, characterized in that: The preparation method of the flame retardant crosslinking agent comprises the following steps: D1, adding tripolyphosphazene chloride, 3,5-dihydroxybenzaldehyde, triethylamine and dimethyl sulfoxide into a reactor, raising the temperature of the reactor to 60-80°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain modified polyether; D2, adding the modified polyether and dimethyl sulfoxide into a reactor and stirring for 10-15 minutes, lowering the temperature of the reactor to 10-15° C., adding sodium borohydride into the reactor, keeping the temperature for reaction for 1-2 hours, and post-treating to obtain the reduced polyether; D3. Add the reduced polyether, epichlorohydrin, sodium carbonate, triethyl borate and ethyl acetate into the reactor, lower the temperature of the reactor to 0-5°C, keep the reaction warm for 1-2h, and post-treat to obtain a flame retardant cross-linking agent.

6. The high-strength and lightweight polyurethane composite material according to claim 5, characterized in that: In step D1, the amount ratio of tripolyphosphazene chloride, 3,5-dihydroxybenzaldehyde, triethylamine and dimethyl sulfoxide is 8-10g:3-5g:0.3-0.5g:40-50mL; in step D2, the amount ratio of modified polyether, dimethyl sulfoxide and sodium borohydride is 5-6g:15-20mL:1-1.6g; in step D3, the amount ratio of reduced polyether, epichlorohydrin, sodium carbonate, triethyl borate and ethyl acetate is 8-10g:4-5g:1-2g:0.3-0.5g:40-60mL.

7. The high-strength and lightweight polyurethane composite material according to claim 1, characterized in that: The preparation method of the flame retardant curing agent comprises the following steps: E1. Add 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde and dimethyl sulfoxide into a reaction kettle and stir for 10-15 minutes, then lower the temperature of the reaction kettle to 10-15°C, add sodium borohydride into the reaction kettle, keep the temperature for reaction for 1-2 hours, and perform post-treatment to obtain modified boric ester; E2. Add modified boric ester, 3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and deionized water into a reactor, increase the temperature of the reactor to 30-50°C, and heat-preserve for 3-5 hours, and then post-treat to obtain a flame retardant curing agent.

8. The high-strength and lightweight polyurethane composite material according to claim 7, characterized in that: In step E1, the amount ratio of 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)benzaldehyde, dimethyl sulfoxide and sodium borohydride is 5-6g:15-20mL:1-1.6g; in step E2, the amount ratio of modified boric ester, 3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and deionized water is 5-6g:2-3g:0.3-0.5g:40-60mL.

Citation Information

Patent Citations

  • Flame-retardant wear-resistant thermoplastic polyurethane composite material and preparation method thereof

    CN110964307A